Metodologia para a construção de taxonomia corporativa facetada - Jordânia Quintão Viana (2022)
Businesses are carried out, and institutional decisions are made, based on information that people believe to be reliable, resulting in the creation of knowledge. The development of information technologies provides institutions with options for storing, accessing and retrieving information. However, the process of making information accessible in a corporate environment can be hampered by the lack of adequate instruments, techniques and procedures. The corporate taxonomy is one of the instruments that allow classifying, organizing, representing and retrieving existing documents and information in the corporate context in an efficient and optimized way. Even with the benefits arising from the implementation of corporate taxonomies, they have limitations, as they are restricted and one-dimensional models. Thus, taxonomic structures with more flexible views gained interest, such as faceted taxonomies, with analytical and visualization capabilities, a means to transform the search and navigation experience. In the Information Science literature, there are specific methods and models for building corporate and faceted taxonomies. However, it was verified the incipience of studies that unify methodologies for the construction of faceted corporate taxonomies, so that greater flexibility and dynamics of representation in the different application domains is possible, through procedures for the construction of this type of taxonomy. In this context, we have the following research question: how to re-signify a previously defined Corporate Taxonomy construction methodology, considering characteristics and attributes of the faceted approach? And, as an objective, we sought to propose theoretical procedures and the systematization of steps of a methodology for the construction of corporate taxonomy, resignifying them and characterizing them as faceted, defining the necessary characteristics for the elaboration of faceted taxonomies in corporate environments, providing the essential elements and attributes for the elaboration, development and maintenance of faceted taxonomies in corporate domains. The methodology is characterized as qualitative, with exploratory and descriptive objectives, and of an applied nature. The methodological procedures included a narrative review of the literature that allowed the identification, location, compilation, analysis and interpretation of knowledge from different sources, in which a cut was made, bringing methodological inputs from the studies that presented proposals for the elaboration of instruments of representation of the faceted knowledge. As a result, the corporate taxonomy model was converted into a taxonomy with a faceted approach, with systematized procedures for the application of the proposed model. As a contribution to the field of Information Science, this investigation brought reflections and inputs that guide the application of the principles and canons of the Faceted Classification Theory in the construction of corporate taxonomies. In the professional sphere, this study contributes by bringing the contributions of the faceted approach to a corporate taxonomy model, a strategic element in supporting information management in organizations.